Analisis Lapisan Hard Chrome dengan Heat Treatment terhadap Kekerasan dan Struktur Mikro pada Permukaan Baja Karbon S45C - Bambang Hari Priyambodo; Margono Margono; Kacuk Cikal Nugroho (Universitas Muhammadiyah Yogyakarta, 2021)
Generally, metals are easy to wear, so material modification is needed to increase hardness to increase the material's resistance to wear and tear. One way is to do a hard chrome plating process using the electroplating method and then continue the heat treatment process. This research was conducted to observe changes in the mechanical properties and microstructure of S45C steel that underwent hard chrome and heat treatment processes. This research was conducted by inserting S45C steel as a cathode into hard chrome liquid and using lead (Pb) as the anode. A positive (+) current powers the anode, the cathode has a negative current (-), the voltage used is 12 V with a duration of 60 minutes. After the cathode was coated with hard chrome, a hardness test was carried out, then continued with the heat treatment process using a temperature of 850°C for 30 minutes. The hardness test results show an increase in the hardness of S45C steel that has been coated with hard chrome, with a hardness value of S45C steel 202.70 VHN, S45C hard chrome steel 998.63 VHN. The highest hardness value is S45C steel coated with hard chrome 998.63 VHN, increasing 392.7%. Then the heat treatment process experienced a decrease in the hardness value, 528.90 VHN, with a percentage of 88.81%. The results of the microstructure observation showed that the hard chrome layer that had been heated treated showed even cracks in the hard chrome layer.